Laser Application in Iran Urology: A Narrative Review - Razzaghi, Mohammad Reza; Fallahkarkan, Morteza; Ghiasy, Saleh; Javanmard, Babak (Journal of Lasers in Medical Sciences, 2017)
The usage of laser in medicine is not recent, and its history in urology goes back to 40 years ago. For the last 2 decades, common uses of laser have been treatments of subjects with urolithiasis, bladder tumors, benign prostatic enlargement, lesions of the genitalia and urinary tract strictures. To evaluate laser application in urology in Iran, we reviewed all of the Iranian literature on the topic. This study was designed to retrieve all studies on laser application in urology in Iran, regardless of publication status or language, covering years 1990–2017. Twenty-six articles were identified: 12 about urolithiasis, 8 about benign prostatic hyperplasia (BPH), 2 case reports, 1 paper about prostate cancer, 1 on female urethral stricture, 1 review and 1 basic sciences study. We conclude that the use of this technology has not yet found its position in Iran, especially in the field of urology. The main causes for it are the difficult accessibility and disturb of laser devices and its accessories, as well as the lack of adequate knowledge of the medical community about this modality.